A Model-based Fiscal Taylor Rule and a Toolkit to Assess the Fiscal Stance - Fournier, Jean-Marc.; Lieberknecht, Philipp (Washington, D.C. : International Monetary Fund, 2020)
This paper presents a model-based fiscal Taylor rule and a toolkit to assess the fiscal stance, defined as the change in the structural primary balance. This is built on the normative buffer-stock model of the government (Fournier, 2019) which includes key channels like hysteresis, cycle-dependent multipliers and a risk premium. A simple fiscal Taylor rule prescribes the fiscal stance as a function of past government debt, past output gap and the past structural primary balance. Applications suggest several advanced economies could have better managed their fiscal stance over the last 20 years. Simulations provide fiscal stance recommendations over the medium-term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet